Assessing Impacts of Alternative Renewable Energy Strategies - d'Artis Kancs; Hans Kremers (Economics and Econometrics Research Institute (EERI), 2002)
The preparation, implementation, coordination and verification of policy measures is a complex and difficult process. This paper presents the first results of an empirical ex-ante analysis which evaluates the effects of renewable energy policies on the bioenergy sector applying an Applied General Equilibrium model. The empirical results suggest that the bioenergy sector benefits more from an indirect tax reduction than from the removal of fossil energy sector subsidies. Reductions in fossil energy sector output below the reference case (base run) do not impact on all fossil energy sectors equally. The crude oil and natural gas sectors lose less (gain more) compared to other fossil energy sectors by implementing renewable energy policy measures.
Keywords: D58; C61; Q15; Q23; Q26; Q40; Q54; 330; Biofuels; CGE model; computational economics; applied general equilibrium; climate policy